Understanding your two-year-old - Miller, Lisa, 1939- (Understanding your child series., 2004)
What makes children in their 'terrible twos' behave as they do? How can parents decide when their child is ready for day care, and manage their child's transition to a trusted child minder? Lisa Miller guides parents through their two-year-old's development, from how to deal with a 'bossy boots' to understanding the central importance of toys, and the development of language and nonverbal communicative skills. She describes ways in which parents can help a young child express or resolve difficult feelings or jealousy, come to accept and welcome a new-born sibling, and negotiate friendships.